Correlation Among The Criterion Of The Professor And The Academic Results In Molecular Biology - Abreu Ugarte, Jorge Eduardo; Saldaña Bernabeu, A.; Benavides Socarras, O. E.; Cruz García, M. A. (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: The methodological work of the department of morfofisiología loans special attention to the quality of the educational process. One of the purposes is the suitable employment of the valued criterion of the professor like a focus of the efficiency of the process, that it is useful to his time also for the prediction of the educational results, in the individual and collective. Objective:The present work studies the correlation of the valued criterion of the professor with the achievement of the aims of the subjects, expressed this last by the educational results obtained in the ordinary examination. It was studied its chronological behavior in the period of five years Material and Methods: A matrix of correlation was created. We determined the coefficient of Spearman. Some factors that could influence in its objectivity predict were also identified by the study. Results:The review of the registers of methodological meetings, open classes and newspapers of classes allowed us to identify some factors that could act on the valued criterion of the professor. They can improve the objectivity of the correlation between this criterion and the academic achieving at the final examination in the subject of molecular biology in the students of first year on medicine career. Conclusions: To attention and systematic monitory of the individual educational evolution and collective in the methodological work of the subject and in the department, attains to increase the efficiency of the valued criterion of the professor and its correlation with the ends academic results. The results constitute an educational innovation for the methodological work in the subjects that integrate the Biological Bases of the Medicine.